A new floating FDNR circuit using differential voltage current conveyors - Sedef, H; Acar, C (URBAN & FISCHER VERLAG, 2000)
A new floating FDNR circuit is proposed using two differential voltage current conveyors and a minimum number of passive elements. Since passive elements are all grounded, this circuit is suitable for fully integrated circuit design. Moreover it does not require any element matching condition. It has a good sensitivity performance due to tracking errors. Finally the proposed FDNR circuit can be controlled through a grounded resistor.
Keywords: floating frequency dependent negative resistor; differential voltage current conveyors and resistively terminated ladder network simulation; 2 CURRENT CONVEYORS; REALIZATION; Engineering; Telecommunications